Conformal Patch Antenna Arrays Design for Onboard Ship Deployment Using Genetic Algorithms. (12th March 2013) - Mitilineos, Stelios A.; Symeonidis, Symeon K.; Mpatsis, Ioannis B.; Iliopoulos, Dimitrios; Kliros, Georgios S.; Savaidis, Stylianos P.; Stathopoulos, Nikolaos A.
Abstract : Conformal antennas and antenna arrays (arrays) have become necessary for vehicular communications where a high degree of aerodynamic drag reduction is needed, like in avionics and ships. However, the necessity to conform to a predefined shape (e.g., of an aircraft's nose) directly affects antenna performance since it imposes strict constraints to the antenna array's shape, element spacing, relative signal phase, and so forth. Thereupon, it is necessary to investigate counterintuitive and arbitrary antenna shapes in order to compensate for these constraints. Since there does not exist any available theoretical frame for designing and developing arbitrary-shape antennas in a straightforward manner, we have developed a platform combining a genetic algorithm-based design, optimization suite, and an electromagnetic simulator for designing patch antennas with a shape that is not a priori known (the genetic algorithm optimizes the shape of the patch antenna). The proposed platform is further enhanced by the ability to design and optimize antenna arrays and is intended to be used for the design of a series of antennas including conformal antennas for shipping applications. The flexibility and performance of the proposed platform are demonstrated herein via the design of a high-performance GPS patch antenna.